Behavioral health interventions for pediatric acute lymphoblastic leukemia: a scoping review - Bates, Carolyn R.; Gibson, Sydney M.; Johnson, Peter R.; Hunt, Sarah L.; Dyjak, Patrick M.; Gibson, Courtney A.; Sharkey, Christina M.; Klages, Kimberly L. (Frontiers in Oncology, 2025)
BackgroundAcute Lymphoblastic Leukemia (ALL) is the most common pediatric cancer, with significant advancements in treatment leading to over 90% five-year event-free survival rates in developed countries. However, disruptions in health behaviors during treatment, such as diet, activity, and sleep, can negatively impact treatment tolerance and increase risks of late effects. This scoping review aimed to assess the breadth of existing behavioral health interventions designed to improve immediate and long-term health outcomes for children and adolescents receiving treatment for ALL.MethodThe review focused on behavioral interventions for children (ages 2–18 years) undergoing active treatment for ALL. We followed the JBI Manual of Evidence Synthesis and PRISMA-ScR guidelines, including a comprehensive search across PubMed, Elsevier, and Web of Science databases. Articles were screened, assessed, and data extracted by multiple reviewers to identify behavioral health promotion interventions used during ALL treatment.ResultsA total of 157 full-text articles were screened, and 86 met inclusion criteria. Most interventions targeted physical activity and exercise (n=36), procedural distress (n=24), nutrition (n=8), and symptom reduction/management (n=6), with others targeting pain, sleep, and health-related quality of life. Date of publication, methodology, and behavioral intervention components varied considerably across studies.ConclusionsThe literature on behavioral health promotion interventions during pediatric ALL treatment is broad but lacks depth, with many studies limited by small sample sizes and stalling at the feasibility stage. There is a need for larger, more rigorous trials to assess the effectiveness of these interventions and improve outcomes for youth with ALL.